Proceedings of the Sixth ACM International Conference on Web Search and Data Mining 2013
DOI: 10.1145/2433396.2433434
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing atypical web search sessions

Abstract: Most research in Web search personalization models users as static or slowly evolving entities with a given set of preferences defined by their past behavior. However, recent publications as well as empirical evidence suggest that for a significant number of search sessions, users diverge from their regular search profiles in order to satisfy atypical, limitedduration information needs. In this work, we conduct a large-scale inspection of real-life search sessions to further understand this scenario. Subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…(For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.) atypical Web search sessions ( Eickhoff, Collins-Thompson, Bennett, & Dumais, 2013 ) are being produced by users with atypical information needs, i.e. those outside their regular areas of expertise (often triggered by external events, such as pending medical treatments, financial deadlines or upcoming vacations); exploring sessions ( Awadallah, White, Dumais, & Wang, 2014 ) are those where users are engaged in an open-ended and multi-faceted information-seeking task to foster learning and discovery; struggling sessions ( Awadallah et al, 2014 ) are those where users are experiencing difficulty locating the required information.…”
Section: Resultsmentioning
confidence: 99%
“…(For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.) atypical Web search sessions ( Eickhoff, Collins-Thompson, Bennett, & Dumais, 2013 ) are being produced by users with atypical information needs, i.e. those outside their regular areas of expertise (often triggered by external events, such as pending medical treatments, financial deadlines or upcoming vacations); exploring sessions ( Awadallah, White, Dumais, & Wang, 2014 ) are those where users are engaged in an open-ended and multi-faceted information-seeking task to foster learning and discovery; struggling sessions ( Awadallah et al, 2014 ) are those where users are experiencing difficulty locating the required information.…”
Section: Resultsmentioning
confidence: 99%
“…Short-term user information plays the same role as the long-term profile in terms of providing additional information for the system to personalize search results (c.f., Shen, Tan, & Zhai, 2005b), and studies (e.g., Bennett et al, 2012;Eickhoff, Collins-Thompson, Bennett, & Dumais, 2013) have found that combining both could improve personalization performance (more see subsection "RLb. Although user profiling is usually for long-term modeling of a user's constant and general interests and preferences, the user's instant information need that can be learned for short-term modeling is not always stored in a profile.…”
Section: User Modelingmentioning
confidence: 99%
“…However, Bennett et al (2012) found that historic behaviors provided substantial benefits at the start of a search session; short-term session behaviors contribute most gains in an extended search session; and the combination of session and historic behaviors outperformed either alone. Eickhoff et al (2013) characterized and personalized search for atypical search sessions, that is, instances when users diverge from their search profiles to satisfy information needs outside their regular areas of interest. They found that certain topics such as medical information and technical support were much more likely to arise in atypical sessions, along with query features such as increased term count, more unique terms, and more natural language-type terms.…”
Section: Rlb Personalization Using Search Behaviorsmentioning
confidence: 99%
“…For instance, during a session search the user's contextual search preference can be updated based on their observed actions [224]; their physical location [41] or their search history can be used to personalize search results and identify when they are behaving atypically [79]. For instance, during a session search the user's contextual search preference can be updated based on their observed actions [224]; their physical location [41] or their search history can be used to personalize search results and identify when they are behaving atypically [79].…”
Section: Dynamics In Information Retrievalmentioning
confidence: 99%